Investigating the motivational teaching strategies of an English native speaker lecturer - Soviyah Soviyah (Teaching English as a Foreign Language Journal, 2022)
Motivation plays a very important role in the success of learning a foreign language. Motivation can come from the teacher. Ways a teacher uses to increase students’ motivation in learning a foreign language are called Motivational Teaching Strategies. The aims of this research are to investigate the motivational teaching strategies used by an English native speaker lecturer and to know the students’ responses toward the Motivational Teaching Strategies used by an English native speaker lecturer. The type of this study is a qualitative research. The subjects involved are an English native speaker lecturer and 23 students of the third semester of the English Education Department, Universitas Ahmad Dahlan Yogyakarta. To collect the data, it was done using classroom observation, interview, and classroom survey.  The research was conducted in Universitas Ahmad Dahlan during the pre-pandemic, around the end of 2019 and the beginning of 2020. To analyze the data, qualitative descriptive was utilized as the main technique. Using Dornyei’s framework of Motivational Teaching Strategies containing 48 items, the results of this study showed that the English native speaker lecturer applied almost all of the strategies of the Motivational Teaching Strategies by Dornyei (2001), which are divided into four categories:  creating the basic motivational conditions, generating initial motivation strategies, maintaining and protecting motivation, and encouraging positive retrospective self-evaluation. There were few strategies, however, that were not yet implemented because of some considerations.  In terms of the students‟ responses, the students mostly saw and agreed that the English native speaker lecturer applied the Motivational Teaching Strategies in the classroom.